A (re) contrução de uma prática alfabetizadora frente aos desafios de pesquisar as relações de ensino e aprendizagem em sala de aula - Filippi, Adriana (2009)
This work has as its study object the teaching practices and relationships of teachinglearning incorporated in the discursive dynamics of the classroom, before the challenges of understanding/ownership of new knowledge from the intervention, the exchange and dialogue with a 1st year group of a local public school in the City of Saudades-SC. The study seeks to analyze how the production of knowledge is in the interactive dynamics of the classroom and its influence on the teaching organization, also aiming to construct and deconstruct hypotheses (concepts) about the teacher´s role as a researcher in her own practice. The exhibition is structured around three areas: teacher training, teaching practice and the learning process of reading and writing. It is analyzed four episodes developed in the classroom, in dialogic and interactive situation and aligned around the use of different kinds of texts. The episodes are retrieved through autoscopy - recordings produced and analyzed by the researcher as a literacy class teacher - and written records, featuring some of the expectations, limitations, advances and changes that go through my practice. The analysis show that it is needed to constantly be in the process of professional and personal development, building knowledge about the practice, meaning the other in order to understand it, giving a sense to the educational action, and considering the relation between theory and practice as a partner in discussions and reconstruction of pedagogical practice